Enzymatic synthesis of geranyl acetate in batch and fed-batch reactors and evaluation of its larvicidal activity against Rhipicephalus (Boophilus) microplus - Remonatto, Daniela [UNESP]; Fantatto, Rafaela Regina [UNESP]; Pietro, Rosemeire Cristina Linhari Rodrigues [UNESP]; Monti, Rubens [UNESP]; Oliveira, J. Vladimir; de Paula, Ariela Veloso [UNESP]; Bassan, Juliana Cristina [UNESP] (Elsevier, 2022)
Geraniol esters, such as geranyl acetate, are known to have antimicrobial and insect-repellent action, but their acaricidal activity has been little explored. This study aimed to investigate the solvent-free synthesis of geranyl acetate in batch (BSTR) and fed-batch (FBSTR) stirred tank reactors using the immobilized lipases NS 88011 and Novozym 435 and evaluate its larvicidal activity against the cattle tick Rhipicephalus (Boophilus) microplus. A central composite design (CCD) was used to maximize the synthesis of geranyl acetate in a BSTR. The independent variables were temperature reaction (40–60 °C), acetic acid/geraniol molar ratio (1:1–1:3), and enzyme loading (1–5% w/w in relation to the substrates). Novozym 435 yielded the best results, achieving 99% of geranyl acetate conversion using 1:3 acetic acid/geraniol molar ratio, 60 °C and 5% (w/w) of enzyme loading after 1 h of reaction in a BSTR. In the FBSTR system, a high content of geranyl acetate was obtained (about 80%) in 4 h of reaction using a 1:1 acetic acid/geraniol molar ratio, 60 °C and 5% (w/w) Novozym 435. Geranyl acetate showed potential as an acaricide, with an LC90 of 6.25 mg/mL and 100% mortality at a concentration of 12.5 mg/mL.
Keywords: Esterification; Fed-batch; Geraniol; Geranyl acetate; Larvicidal; Lipase